A comparative study of hydroxyl‐ and carboxylate‐functionalized imidazolium and benzimidazolium salts as precursors for N‐heterocyclic carbene ligands. (15th July 2015) - Allegue, Andrés; Albert‐Soriano, María; Pastor, Isidro M.
<x xml:space="preserve">Abstract</x> The preparation of imidazolium and benzimidazolium salts with hydroxyl or carboxylate functions has been achieved using straightforward synthetic pathways. These salts in combination with palladium(II) acetate give active catalytic systems for Suzuki reaction. A comparative study has been performed, which has revealed that both the heterocycle and the functional group are important for the catalytic activity and stability of the catalyst. Copyright © 2015 John Wiley & Sons, Ltd.